Hot bats go cold: Heterothermy in neotropical bats - Czenze, Z.J.; Dunbar, M.B. (Canadian Journal of Zoology, 2017)
Torpor is common in bats, but has historically been viewed as an energy-saving technique reserved for temperate and subarctic climates; however, torpor use is common across several tropical bat families. Central America hosts a great diversity of bats with approximately 150 species, yet data from this area are lacking compared with tropical Africa and Australia. We investigated thermoregulatory responses of bats from neotropical Belize and captured adult bats in the tropical forests of Lamanai Archeological Reserve, Belize. After a 12 h acclimation period, we recorded rectal temperature prior to and after exposing bats to an ambient temperature (Ta) of 7 °C forupto 2 h in anenvironmental chamber. All 11 species across four families expressed torpor to some degree upon exposure to cool temperatures. Individuals from Vespertilionidae defended the lowest resting body temperature (Tb) and showed the greatest decrease in Tb after acute exposure to low Ta. Our data help to establish a new spectrum of physiological ability for this group of mammals and shed light on the evolution of torpor and heterothermy. Weshow that energy conservation is important even in warm and energetically stable environmental conditions. Understanding how and why torpor is used in warm climates will help to better define paradigms in physiological ecology. © 2017, Canadian Science Publishing. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: Africa; Australia; Bats; Belize; Belize [Central America]; Central America; Heterothermy; Lamanai; Mammalia; Neotropical Region; Orange Walk; Torpor; Tropics; Vespertilionidae; acclimation; bat; body temperature; dept.bio; ecophysiology; energy conservation; environmental conditions; physiological response; thermoregulation; torpor; tropical forest; tropical region

Genome sequences of Chancellor, Mitti, and Wintermute, three subcluster K4 phages isolated using Mycobacterium smegmatis mc ^2 155 - Edgington, Nicholas P.; Voshell, Stephanie M.; Ware, Vassie C.; Akoto, Francis F.; Alhout, Alexa A.; Atwal, Gurvina J.; Balyozian, John B.; Cadieux, Zachary A.; Chop, Brianna M.; Cresawn, Steven G.; Cudkevich, Netta; Faltine-Gonzalez, Dylan Z.; et al. (Genome Announcements, 2017)
Mycobacteriophages Chancellor, Mitti, and Wintermute infect Mycobacterium smegmatis mc2155 and are closely related to phages Cheetobro and Fionnbharth in subcluster K4. Genome sizes range from 57,697 bp to 58,046 bp. Phages are predicted to be temperate and to infect the pathogen Mycobacterium tuberculosis. © 2017 Edgington et al.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-598-311-527-674, pop00117 tex.type: [object Object]
Keywords: Mycobacterium smegmatis; Mycobacterium tuberculosis; dept.bio; genome size; infectious agent; mycobacteriophage; nonhuman

Environmental exposure does not explain putative maladaptation in road-adjacent populations. - Brady, Steven P (Oecologia, 2017)
While the ecological consequences of roads are well described, little is known of their role as agents of natural selection, which can shape adaptive and maladaptive responses in populations influenced by roads. This knowledge gap persists despite a growing appreciation for the influence of evolution in human-altered environments. There, insights indicate that natural selection typically results in local adaptation. Thus, populations influenced by road-induced selection should evolve fitness advantages in their local environment. Contrary to this expectation, wood frog tadpoles from roadside populations show evidence of a fitness disadvantage, consistent with local maladaptation. Specifically, in reciprocal transplants, roadside populations survive at lower rates compared to populations away from roads. A key question remaining is whether roadside environmental conditions experienced by early stage embryos induce this outcome. This represents an important missing piece in evaluating the evolutionary nature of this maladaptation pattern. Here, I address this gap using a reciprocal transplant experiment designed to test the hypothesis that embryonic exposure to roadside pond water induces a survival disadvantage. Contrary to this hypothesis, my results show that reduced survival persists when embryonic exposure is controlled. This outcome indicates that the survival disadvantage is parentally mediated, either genetically and/or through inherited environmental effects. This result suggests that roadside populations are either truly maladapted or potentially locally adapted at later life stages. I discuss these interpretations, noting that regardless of mechanism, patterns consistent with maladaptation have important implications for conservation. In light of the pervasiveness of roads, further resolution explaining maladaptive responses remains a critical challenge in conservation.
14 citations (Crossref) [2023-10-31] Place: Germany Brady, Steven P. School of Forestry & Environmental Studies, Yale University, 370 Prospect Street, New Haven, CT, 06511, USA. brady.steven@gmail.com. Brady, Steven P. Biology Department, Southern Connecticut State University, New Haven, CT, 06515, USA. brady.steven@gmail.com.
Keywords: *Adaptation; Physiological; *Environmental Exposure; *Ranidae; *Selection; Genetic; Acclimatization; Adaptation; Physiological; Amphibia; Amphibians; Animals; Contemporary evolution; Environmental Exposure; Inherited environmental effects; Larva; Local adaptation; Rana sylvatica; Ranidae; Ranidae/ph [Physiology]; Runoff; Selection; Genetic; acclimatization; adaptation; amphibian; animal; dept.bio; embryonic development; environmental conditions; environmental effect; environmental exposure; evolutionary biology; fitness; frog; genetic selection; larva; local adaptation; natural selection; physiology; pond; population type; roadside environment; runoff; survival

Positive sire effects and adaptive genotype by environment interaction occur despite pattern of local maladaptation in roadside populations of an amphibian - Brady, Steven P.; Goedert, Debora (Copeia, 2017)
The global road network causes many negative ecological effects. Contrasting our knowledge of these effects, insights into evolutionary consequences of roads remain undeveloped. Here, we study a suite of populations of the Wood Frog that appear to be evolving maladaptively in response to road-adjacency. Specifically, when raised together in roadside pools, roadside populations survive at lower rates compared to populations away from roads. To begin to understand the cause of this survival disadvantage, we investigated potential parental and genetic sources of maladaptation. First, to assess whether parental effects might induce maladaptation, we measured adult body weight to length ratio ('relative weight') and its influence on offspring survival in a reciprocal transplant experiment across 12 populations. Next, to assess whether genetic effects might limit adaptive responses in offspring, we estimated genetic correlations between environments for survival and fitness-related traits. We found that relative weight was higher in roadside populations and, for males, had a positive influence on offspring survival. This demonstrates a novel transgenerational effect of Wood Frog adult males but suggests that this effect is not causing maladaptive survival. Genetic correlations indicated that a subset of roadside genotypes respond adaptively to road-adjacency despite population level maladaptive survival. This suggests that metapopulation dynamics and/or high levels of nonadditive genetic variance may be limiting adaptation or that insufficient time has elapsed for adaptation to occur. Together, these results highlight the complexity and scale of responses to a pervasive feature of landscape alteration revealed by evolutionary approaches.
6 citations (Crossref) [2023-10-31]
Keywords: Amphibia; Rana sylvatica; adaptation; amphibian; dept.bio; environmental conditions; evolutionary biology; frog; genotype; genotype-environment interaction; heritability; local adaptation; metapopulation; population type; roadside environment; survival

How valid are old species lists? How archived samples can be used to update Ephemeroptera biodiversity information for northern Canada - Giberson, Donna J.; Burian, Steven K. (The Canadian Entomologist, 2017)
Abstract Broad-scale aquatic insect ecological studies are an important potential source of biodiversity information, though taxa lists may contain outdated names or be incompletely or incorrectly identified. We re-examined over 12 000 archived Ephemeroptera (mayfly) specimens from a large environmental assessment project (Mackenzie Valley pipeline study) in Yukon and the Northwest Territories, Canada (1971–1973) and compared the results to data from five recent (post-2000) collecting expeditions. Our goals were to update the species list for Ephemeroptera for Yukon and the Northwest Territories, and to evaluate the benefits of retaining and re-examining ecological samples to improve regional biodiversity information, particularly in isolated or inaccessible areas. The original pipeline study specimen labels reported 17 species in 25 genera for the combined Yukon and Northwest Territories samples, of which six species and 15 genera are still valid. Re-examination of specimens resulted in 45 species in 29 genera, with 14 and seven newly recorded species for Northwest Territories and Yukon, respectively. The recent collecting resulted in 50 species, 29 of which were different from the pipeline study, and five of which were new territorial records (Northwest Territories: four species; Yukon: one species). Re-examination of archived ecological specimens provides a cost-effective way to update regional biodiversity information.
4 citations (Crossref) [2023-10-31]
Keywords: Canada; Ephemeroptera; Hexapoda; Mackenzie Valley; Northwest Territories; Yukon Territory; aquatic organism; biodiversity; dept.bio; environmental assessment; information; mayfly; new record; sampling; species inventory

Range extensions for recently described North American species of Acentrella Bengtsson (Insecta: Ephemeroptera: Baetidae) - Webb, Jeffrey M.; Burian, Steven K. (Check List, 2017)
New state records are provided for two recently described species of North American Acentrella Bengtsson, 1912. Acentrella nadineae McCafferty, Waltz & Webb, 2009 is newly reported from Connecticut, Massachusetts, and Minnesota, and A. rallatoma Burian & Myers, 2011 is reported from Minnesota.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/103-027-562-874-776, pop00306 tex.type: [object Object]
Keywords: Mayfly; Nearctic; New records; Range extension; dept.bio; mayfly; new records; range extension

Antimicrobial evaluation of 5-substituted aryl 1H-tetrazoles - Feinn, Liana; Dudley, Joshua; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2017)
Background: Tetrazole derivatives such as 1-substituted dinitrobenzyl tetrazoles and their oxa and selanyl analogs have previously been studied against drug-susceptible and multidrugresistant mycobacteria. In addition, other tetrazole derivatives have been shown to inhibit CTX-M class A μ-lactamases. Objective: To study the antibacterial activity of 5-substituted aryl 1H-tetrazole derivatives. Methods: The antibacterial activity of several known 5-substituted aryl 1H-tetrazole derivatives was evaluated against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The activity was assessed by determining the minimum inhibitory concentration of these tetrazole derivatives and comparing them to the known antibiotics amoxicillin, trimethoprim and sulfamethoxazole. Results: Some derivatives showed significant antibacterial activity with the most active derivatives exhibiting a minimum inhibitory concentration (MIC) of 125-250 μg/mL against Staphylococcus aureus and Escherichia coli. Using some of these tetrazole compounds in combination with trimethoprim led to a synergistic effect that gave MIC values ranging from 0.24-1.95 μg/mL against Escherichia coli and 3.91-31.3 μg/mL against Staphylococcus aureus. The tetrazole derivatives were prepared in an isopropanol/water mixture using microwave heating at 160 °C for 1h. The cycloaddition between organonitriles and sodium azide was catalyzed by indium chloride. Conclusion: This study shows a significant synergistic effect between the tetrazole compounds tested and trimethoprim which could be used to potentially develop new antibacterial agents. © 2017 Bentham Science Publishers.
4 citations (Crossref) [2023-10-31]
Keywords: 1; 4 di(tetrazol 5 yl)benzene; 2 propanol; 4 acetylbenzonitrile; 4 acetylbenzotetrazole; 4 bromobenzotetrazole; 5 substituted aryl tetrazole derivative; 5-substituted 1H-tetrazoles; Antibacterial activity; Antimicrobial activity; Article; Escherichia coli; Indium chloride; Microwave chemistry; Pseudomonas aeruginosa; Staphylococcus aureus; [2 + 3] cycloaddition; amoxicillin; antibacterial activity; antibiotic agent; catalysis; clinical assessment; comparative study; controlled study; cycloaddition; dept.bio; dept.che; drug effect; drug screening; drug structure; indium chloride; microwave cooking; minimum inhibitory concentration; nonhuman; peer-reviewed; priority journal; reaction analysis; sodium azide; sulfamethoxazole; tetrazole derivative; trimethoprim; unclassified drug; water

Winter Quiescence, Growth Rate, and the Release from Competition in the Temperate Scleractinian Coral Astrangia poculata (Ellis & Solander 1786) - Grace, Sean (Northeastern Naturalist, 2017)
I examined winter quiescence (dormancy), growth rate, and competition in the scleractinian coral Astrangia poculata (Northern Star-coral) at an intertidal and a subtidal site in Rhode Island. I observed the onset, duration, and cessation of quiescence from November 2013 to May 2014 and noted when coral tentacles no longer exhibited tactile responses, which I used as a proxy for quiescence. Results demonstrated that intertidal corals entered quiescence in December 2013, when air/water temperatures ranged from 0.71 °C to 5.7 °C, whereas subtidal populations entered quiescence in January when water temperatures ranged from 3.4 °C to 4.3 °C. Corals exited quiescence at similar temperatures (6.0–8.5 °C), again doing so earlier in the intertidal than subtidal populations (April and May 2014, respectively). Corals at both sites grew (added polyps) over the course of the study, but during quiescence, growth ceased in subtidal corals, and intertidal corals lost peripheral polyps. Competitive interactions between Northern Star-coral and the tunicate Didemnum vexillum (Carpet Tunicate) decreased during quiescence with a corresponding increase in “halo” width around each coral. I observed no change in halo-width between coral and the sponge Cliona celata (Red Boring Sponge). All corals examined exhibited winter quiescence, grew during the course of the study, and were released from competition with Carpet Sea-squirt Tunicate; no change in competition with Red Boring Sponge was observed.
18 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/116-846-890-414-593, pop00163 tex.type: [object Object]
Keywords: dept.bio; peer-reviewed

Prophage-mediated defence against viral attack and viral counter-defence. - Dedrick, Rebekah M; Jacobs-Sera, Deborah; Bustamante, Carlos A Guerrero; Garlena, Rebecca A; Mavrich, Travis N; Pope, Welkin H; Reyes, Juan C Cervantes; Russell, Daniel A; Adair, Tamarah; Alvey, Richard; Bonilla, J Alfred; Bricker, Jerald S; et al. (Nature Microbiology, 2017)
Temperate phages are common, and prophages are abundant residents of sequenced bacterial genomes. Mycobacteriophages are viruses that infect mycobacterial hosts including Mycobacterium tuberculosis and Mycobacterium smegmatis, encompass substantial genetic diversity and are commonly temperate. Characterization of ten Cluster N temperate mycobacteriophages revealed at least five distinct prophage-expressed viral defence systems that interfere with the infection of lytic and temperate phages that are either closely related (homotypic defence) or unrelated (heterotypic defence) to the prophage. Target specificity is unpredictable, ranging from a single target phage to one-third of those tested. The defence systems include a single-subunit restriction system, a heterotypic exclusion system and a predicted (p)ppGpp synthetase, which blocks lytic phage growth, promotes bacterial survival and enables efficient lysogeny. The predicted (p)ppGpp synthetase coded by the Phrann prophage defends against phage Tweety infection, but Tweety codes for a tetrapeptide repeat protein, gp54, which acts as a highly effective counter-defence system. Prophage-mediated viral defence offers an efficient mechanism for bacterial success in host-virus dynamics, and counter-defence promotes phage co-evolution.
175 citations (Crossref) [2023-10-31] Place: England Dedrick, Rebekah M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Bustamante, Carlos A Guerrero. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Reyes, Juan C Cervantes. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Adair, Tamarah. Department of Biology, Baylor University, Waco, Texas 76798, USA. Alvey, Richard. Biology Department, Illinois-Wesleyan University, Bloomington, Illinois 61702, USA. Bonilla, J Alfred. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Bricker, Jerald S. Biology Department, Nebraska-Wesleyan University, Lincoln, Nebraska 68504, USA. Brown, Bryony R. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Byrnes, Deanna. Biology Department, Carthage College, Kenosha, Wisconsin 53140, USA. Cresawn, Steven G. Biology Department, James Madison University, Harrisonburg, Virginia 22807, USA. Davis, William B. School of Molecular Biosciences, Washington State University Pullman, Washington 99164, USA. Dickson, Leon A. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Edgington, Nicholas P. Biology Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Findley, Ann M. Biology, School of Sciences, University of Louisiana at Monroe, Monroe, Louisiana 71209, USA. Golebiewska, Urszula. Biological Sciences and Geology, Queensborough Community College, Bayside, New York 11364, USA. Grose, Julianne H. Biology Department, Brigham Young University, Provo, Utah 84602, USA. Hayes, Cory F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Hughes, Lee E. Biological Sciences, University of North Texas, Denton, Texas 76203, USA. Hutchison, Keith W. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Isern, Sharon. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Johnson, Allison A. Biology Department, Virginia Commonwealth University, Richmond, Virginia 23284, USA. Kenna, Margaret A. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Klyczek, Karen K. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Mageeney, Catherine M. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Michael, Scott F. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Molloy, Sally D. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Montgomery, Matthew T. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Neitzel, James. Biology Department, The Evergreen State College, Olympia, Washington 98502, USA. Page, Shallee T. Division of Environmental and Biological Sciences, University of Maine-Machias, Machias, Maine 04654, USA. Pizzorno, Marie C. Biology Department, Bucknell University, Lewisburg, Pennsylvania 17837, USA. Poxleitner, Marianne K. Biology Department, Gonzaga University, Spokane, Washington 99258, USA. Rinehart, Claire A. Biology Department, Western Kentucky University, Bowling Green, Kentucky 42101, USA. Robinson, Courtney J. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Rubin, Michael R. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Teyim, Joseph N. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Vazquez, Edwin. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Ware, Vassie C. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Washington, Jacqueline. Department of Biology and Chemistry, Nyack College, Nyack, New York 10960, USA. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA.
Keywords: *Mycobacteriophages/ph [Physiology]; *Mycobacterium smegmatis/vi [Virology]; *Mycobacterium tuberculosis/vi [Virology]; *Prophages/ph [Physiology]; DNA; Viral; DNA; Viral/ge [Genetics]; Genetic Variation; Genome; Bacterial; Genome; Viral; Ligases; Ligases/ge [Genetics]; Lysogeny; Mycobacteriophages; Mycobacteriophages/ge [Genetics]; Mycobacterium smegmatis; Mycobacterium smegmatis/ge [Genetics]; Mycobacterium tuberculosis; Mycobacterium tuberculosis/ge [Genetics]; Phylogeny; Prophages; Prophages/en [Enzymology]; Prophages/ge [Genetics]; Viral Proteins; Viral Proteins/ge [Genetics]; bacterial genome; dept.bio; enzymology; genetic variation; genetics; guanosine 3'; 5'-polyphosphate synthetases; ligase; lysogenization; mycobacteriophage; phylogeny; physiology; prophage; viral protein; virology; virus DNA; virus genome

Physiological consequences of exposure to salinized roadside ponds on wood frog larvae and adults - Hall, Emily M.; Brady, Steven P.; Mattheus, Nichole M.; Earley, Ryan L.; Diamond, Molly; Crespi, Erica J. (Biological Conservation, 2017)
40 citations (Crossref) [2023-10-31]
Keywords: dept.bio

Evolutionary toxicology: Toward a unified understanding of life's response to toxic chemicals. - Brady, Steven P; Monosson, Emily; Matson, Cole W; Bickham, John W (Evolutionary Applications, 2017)
45 citations (Crossref) [2023-10-31] Place: England Brady, Steven P. Biology Department Southern Connecticut State University New Haven CT USA. Monosson, Emily. The Ronin Institute for Independent Scholars and Department of Environmental Conservation University of Massachusetts Amherst MA USA. Matson, Cole W. Department of Environmental Science and Center for Reservoir and Aquatic Systems Research (CRASR) Baylor University Waco TX USA. Bickham, John W. Department of Wildlife & Fisheries Sciences Texas A&M University College Station College Station TX USA.
Keywords: dept.bio; peer-reviewed

Road ecology: shifting gears toward evolutionary perspectives - Brady, Steven P.; Richardson, Jonathan L. (Frontiers in Ecology and the Environment, 2017)
Recent advances in understanding the often rapid pace of evolution are reshaping our view of organisms and their capacity to cope with environmental change. Though evolutionary perspectives have gained traction in many fields of conservation, road ecology is not among them. This is surprising because roads are pervasive landscape features that generate intense natural selection. The biological outcomes from these selection pressures – whether adaptive or maladaptive – can have profound consequences for population persistence. We argue that studying evolutionary responses is critical to accurately understand the impacts of roads. Toward that end, we describe the basic tenets and relevance of contemporary evolution and showcase the few examples where it has been documented in road ecology. We outline practical ways that road ecologists can estimate and interpret evolutionary responses in their research. Finally, we suggest priority research topics and discuss how evolutionary insights can inform conservation in landscapes traversed by roads.
42 citations (Crossref) [2023-10-31]
Keywords: dept.bio; peer-reviewed

Incorporating evolutionary insights to improve ecotoxicology for freshwater species - Brady, Steven P.; Richardson, Jonathan L.; Kunz, Bethany K. (Evolutionary Applications, 2017)
Ecotoxicological studies have provided extensive insights into the lethal and sublethal effects of environmental contaminants. These insights are critical for environmental regulatory frameworks, which rely on knowledge of toxicity for developing policies to manage contaminants. While varied approaches have been applied to ecotoxicological questions, perspectives related to the evolutionary history of focal species or populations have received little consideration. Here, we evaluate chloride toxicity from the perspectives of both macroevolution and contemporary evolution. First, by mapping chloride toxicity values derived from the literature onto a phylogeny of macroinvertebrates, fish, and amphibians, we tested whether macroevolutionary relationships across species and taxa are predictive of chloride tolerance. Next, we conducted chloride exposure tests for two amphibian species to assess whether potential contemporary evolutionary change associated with environmental chloride contamination influences chloride tolerance across local populations. We show that explicitly evaluating both macroevolution and contemporary evolution can provide important and even qualitatively different insights from those obtained via traditional ecotoxicological studies. While macroevolutionary perspectives can help forecast toxicological end points for species with untested sensitivities, contemporary evolutionary perspectives demonstrate the need to consider the environmental context of exposed populations when measuring toxicity. Accounting for divergence among populations of interest can provide more accurate and relevant information related to the sensitivity of populations that may be evolving in response to selection from contaminant exposure. Our data show that approaches accounting for and specifically examining variation among natural populations should become standard practice in ecotoxicology.
34 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-040-409-668-282, pop00101 tex.type: [object Object]
Keywords: LC50; acute exposure; adaptation; chloride; dept.bio; maladaptation; peer-reviewed; road salt runoff

Autism risk: What do vaccines have to do with - Crawford, Sarah Adelaide (Academic Journal of Pediatrics & Neonatology, 2017)
Keywords: dept.bio; ⚠️ Invalid DOI

Using time dynamically in static intervals: Does it close the achievement gap? - Grace, Lori (Learning Environments Research, 2017)
A mixed-methods study was undertaken with 118 biology students in two urban high schools. A Student-Centered Adaptable Learning Environment (SCALE) was created to improve engagement from affective and cognitive perspectives using choice, creativity and technological allowances. Results demonstrated that fast and slow learners are generally separated by about 30 min in terms of inputting speeds, but can be as much as 65 min apart from one another. Given that traditional classrooms afford students only 45 min in which to learn, static time could have become a source of inequity in public schools. SCALE optimally allowed for the dynamic use of time in constrained periods, therefore reducing and even eliminating any negative relationships between speed of learning and resultant achievement gains in the block setting. Especially benefitting from their ability to maneuver were the slowest learners, who showed the largest achievement improvements in either time interval amongst ability groupings. As learning speed can be the most critical contributing component of resultant educational outcomes, providing students the ability to use time dynamically should be considered as a feasible solution to helping teachers reestablish equity in mixed-ability classrooms in public schools. © 2017, Springer Science+Business Media Dordrecht.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-365-031-456-996 tex.type: [object Object]
Keywords: Cognitive levelling; Dynamic time; Educational technology; Learning equity; Learning speed gap; Psychosocial learning environments; dept.bio